Understanding online dual practice of public hospital doctors in China: a mixed-methods study. Issue 4 (18th February 2022) - Xu, Duo; Zhan, Jiajia; Cheng, Terence; Fu, Hongqiao; Yip, Winnie
Abstract: Telemedicine and telehealth hold promise for reducing access barriers, improving quality and containing medical costs. As Internet companies enter the healthcare market, a rising number of online healthcare platforms have emerged worldwide. In some countries like China, public hospital doctors are providing direct-to-consumer telemedicine services on these commercial platforms as independent providers. Such online service provision creates a new form of dual practice, which we refer to as 'online dual practice' in this study. Using a mixed-methods design, this study aims to investigate the prevalence of online dual practice, doctors' time allocation and motivations for engaging in it and its potential impacts on the health system in China. We use the web-crawled data from four leading online health platforms to examine the prevalence of online dual practice in China. Then we conduct in-depth interviews with 38 active doctors on these platforms to investigate their time allocation, motivations and perception regarding online service provision. We find that the nationwide prevalence of online dual practice in China reaches at least 16.5% in 2020 and that it is more common among senior public hospital doctors. Public hospital doctors mainly use small pockets of time during working hours and after-hours to render services on the platforms The five most commonly cited motivations for their engagement in online dual practice are efficiency improvement, personal control, career development, financial rewards and serving the patients. Interviewed doctors believe that their online service provision is conducive to increasing healthcare access and improving efficiency, but some also express their concerns about the quality of care. Further analysis shows that the impact of online dual practice on health system performance remains an open question and regulatory policies on it should be health-system specific.